KEEFEKTIFAN MODEL PROBLEM BASED LEARNING (PBL) BERBANTUAN VIDEO ANIMASI DALAM MENINGKATKAN HASI BELAJAR IPAS PADA SISWA KELAS IV SD NEGERI 1 PELEM BLORA - Evi Nurul Hidayati; Choirul Huda; Henry Januar Saputra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Learning Natural and Social Sciences (IPAS) in elementary schools still faces various obstacles, especially in mastering abstract concepts and learning that tends to be teacher-centered. These conditions have an impact on low learning outcomes and a lack of student activity. This study aims to determine the differences in students' IPAS learning outcomes before and after the implementation of the Problem Based Learning (PBL) model assisted by animated videos, and to analyze the effectiveness of the model in improving the learning outcomes of fourth-grade students at SD Negeri 1 Pelem Blora. This study uses a quantitative approach with an experimental research type, a pre-experimental design in the form of a one-group pretest–posttest design. The subjects of the study were all fourth-grade students of SD Negeri 1 Pelem Blora. Data collection techniques used learning outcome tests, observation, and documentation. Data were analyzed using paired sample t-tests. The results of the study showed a significant difference between students' IPAS learning outcomes before and after the implementation of the PBL model assisted by animated videos. Thus, it can be concluded that the research related to the Problem Based Learning (PBL) learning model assisted by animated videos is effective in improving the science learning outcomes of fourth-grade students at Elementary School 1 Pelem Blora has been successful. This is because students are required to be active as the main actors in learning, the use of animation as a learning medium, the structure of the learning process that helps students construct knowledge and increases student motivation and activeness through animation. This model can be used as an innovative learning alternative to create active, contextual, and meaningful learning in accordance with the demands of the Independent Curriculum.